Influence of Seed Priming Techniques for Enhancing Seed Quality in Sunflower (Helianthus annuus L.) - RAKSHITHA, HN; PARASHIVAMURTHY; HARISH MS (Seed Research, 2026)
Seed priming is one of the economical and feasible technologies for rapid and uniform field emergencein most of the field crops. A laboratory experiment was conducted in the Seed Testing Laboratory, AICRP on Seed(Crops), NSP, University of Agricultural Sciences, GKVK, Bangalore. Out of 14 priming treatments, hydroprimingfor 18 h (T3) recorded highest seed quality parameters like germination (81.80%), shoot length (17.80 cm), rootlength (13.92 cm), mean seedling length (31.09 cm), mean seedling dry weight (21.40 mg), SVI-I (2591) and SVIII (1704). This was followed by priming with 2% KNO3 for 18 h (81.0%, 16.60 cm, 13.86 cm, 29.65 cm, 21.09 mg,2418 and 1673, respectively). Highest (1.16) dehydrogenase activity was recorded in seeds primed with 2%KNO3 for 18 h. Hence, the seed subjected to hydropriming for 18 h and priming with 2% KNO3 for 18 h arepromising for sunflower cultivation.